2014
DOI: 10.1111/ceo.12298
|View full text |Cite
|
Sign up to set email alerts
|

Histological subtypes of periocular basal cell carcinoma

Abstract: Background: To determine the proportion of different subtypes of periocular BCC in South Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
5
13
0
1
Order By: Relevance
“…In comparison, the percentage of aggressive histological types (infiltrative, metatypical, micronodular and desmoplastic) in our group was 49·0%, with the most common aggressive type being micronodular. The distribution of types of BCC in this study was similar, with the exception of a larger proportion of aggressive BCCs, to a large study from South Australia …”
Section: Discussionsupporting
confidence: 83%
“…In comparison, the percentage of aggressive histological types (infiltrative, metatypical, micronodular and desmoplastic) in our group was 49·0%, with the most common aggressive type being micronodular. The distribution of types of BCC in this study was similar, with the exception of a larger proportion of aggressive BCCs, to a large study from South Australia …”
Section: Discussionsupporting
confidence: 83%
“…6,8 This statement can be affirmed in accordance with a retrospective study carried out in Australia for a period of seven years (2006 to 2012) which have discovered BCC occurring more frequently on the lower lid. 6 An early study in central India also demonstrated similar finding.…”
Section: Discussionsupporting
confidence: 53%
“…This finding is particularly constant with previous study in Oradea while interestingly, most other studies describing nodular BCC as the most common histological type. 2,6,9,11 There are limitations in this study where this study may not represent the entire Bandung population. Nonetheless, this study provides a compelling overview of BCC as a basis of upcoming research and essential information for physicians and the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations